2004
DOI: 10.1111/j.1937-5956.2004.tb00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting ISO 14000 Diffusion: A New “Look” at the Drivers of Certification

Abstract: T his replication study of the drivers of ISO 14000 certifications extends the work of Corbett and Kirsch (2001) and provides a different and simpler predictive model of the factors contributing to the growth of ISO 14000 certifications. The main finding is that at national level ISO 14000 certification densities can be explained by two factors: the installed base of ISO 9000 certificates and the number of environmental treaties signed and ratified. The first factor, considering the common elements of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 18 publications
5
45
0
3
Order By: Relevance
“…However, unlike in the case of developed countries, we find that in Romania the potential for collective action in the environmental area is not significant. Whether the influence of stakeholders on PACE will strengthen as Romania completes its development 25 process remains to be seen. Also, there is no evidence that environmental taxes work as incentives to adopt an environmental behaviour at plant level.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike in the case of developed countries, we find that in Romania the potential for collective action in the environmental area is not significant. Whether the influence of stakeholders on PACE will strengthen as Romania completes its development 25 process remains to be seen. Also, there is no evidence that environmental taxes work as incentives to adopt an environmental behaviour at plant level.…”
Section: Discussionmentioning
confidence: 99%
“…A norma ISO 9001, que estabelece os requisitos para o estabelecimento de um Sistema de Gestão da Qualidade, é reconhecida como uma grande influência na decisão de adotar a ISO 14001, com organizações mais propensas a adotar a ISO 14001 em países em que a certificação da qualidade é mais presente (Vastag, 2004). Em um estudo com 56 países, Albuquerque et al (2007) verificaram que, em razão das semelhanças na concepção, na linguagem, na estrutura e na metodologia entre os padrões, a adoção prévia da norma ISO 9001 facilitaria a implantação e contribuiria para uma difusão mais rápida da ISO 14001.…”
Section: Fatores Que Motivam a Difusão Da Iso 14001unclassified
“…Ainda segundo Albuquerque et al (2007, p. 454), esse fenômeno ocorreria pelo fato de a disseminação da ISO 9001 "reduzir as incertezas relacionadas ao valor comercial e à relevância dos padrões de normalização". As semelhanças entre as motivações para adotar as certificações ISO 14001 e ISO 9001 também foram destacadas por Corbett & Kirsch (2001;2004), Vastag (2004) e Viadiu et al (2006).…”
Section: Fatores Que Motivam a Difusão Da Iso 14001unclassified
See 1 more Smart Citation
“…As the requirements for certification typically build upon each other, the existence of one standard makes it easier to adopt the other one as well. Accordingly, several studies showed that organizations with ISO 9000 standards were more likely do adopt also the ISO 14000 standard (e.g., Corbett and Kirsch, 2001;Vastag, 2004). Examples for key questions in this line of inquiry are: What relations between different practices can we distinguish?…”
Section: Future Research Extending the Bourdieusian Approach To Csrmentioning
confidence: 99%